Effect of monocrotaline ingestion on the distribution of protein and angiotensin converting enzyme activity in the rat lung. Issue 12 (December 1986) - Shale, D J; Wiseman, M S; Cookson, W O
Abstract : The alveolar accumulation of protein and angiotensin converting enzyme activity was compared with the development of right ventricular hypertrophy in male rats after different periods of monocrotaline exposure. Total doses of monocrotaline were varied by dividing the animals into three groups in which ingestion was limited to three, seven, and 15 days. These groups were studied 21 days after the start of monocrotaline exposure and compared with a group treated continuously for 28 days. The total lung weight increased after three or more days of treatment, while after seven days there was significant alveolar accumulation of protein, which was paralleled by an increase in angiotensin converting enzyme activity in alveolar lavage fluid. Identical changes also occurred after 15 and 28 days of exposure to monocrotaline. Lung angiotensin converting enzyme activity was decreased after three days' ingestion of monocrotaline and did not alter further with longer periods of exposure. None of these effects of monocrotaline in the three and seven day treatment groups was associated with right ventricular hypertrophy, which occurred only in animals treated for 15 or more days. The effects of monocrotaline ingestion on the lung were dose related and had no causal relationship to the development of right ventricular hypertrophy.